Fortalecimiento de la Cultura Tributaria en la Dirección Nacional de Escuelas de la Policía Nacional de Colombia - Padilla Cajamarca, Leonardo Albeiro; Bautista Murcia, Miguel Fernando (Universidad Antonio Nariño, 2022)
Taking as reference one of the institutions of higher education recognized by the Ministry of National Education, as it is, the National Directorate of Police Academies. The issue of tax culture is addressed, under the approach of knowing the current state of it, not only at the central level but in each of its sections, through the application of a diagnostic instrument. Which is why, using ICTs, it was possible to collect data and certain facts in categories such as morality, education and behavior. Which constitutes the main input to make the appropriate decisions and actions, compared to promoting those issues that sometimes due to ignorance, lack of suitability or simply lack of professional training, can become negative situations during the management of the entire police institution by different agencies that make control in such matters. According to the statement it was obtained as a result a guide document, which gives parameters and regulations guidelines with tax focus. That situation concludes that the entities constantly must be updated for managing efficiently the entrusted activities to the management of the collection.